Hypertension-Related Admissions and Outcome in a Tertiary Hospital in Northeast Nigeria - P. M. Kolo; Y. B. Jibrin; E. O. Sanya; M. Alkali; I. B. Peter Kio; R. K. Moronkola (International Journal of Hypertension)
Cardiovascular disease has reached near epidemic proportion in sub-Saharan Africa, and systemic hypertension (SH) remains the driver of cardiovascular complications. We studied hypertension-related admissions and their outcome at the Abubaker Tafawa Balewa University Teaching Hospital (ATBUTH) Bauchi, Northeast Nigeria. Records of all patients admitted into the medical wards between 1st November 2010 and 31st October 2011 were studied, and case files of those managed for SH complications were selected for detailed examination. Of the total 3108 admissions, 735 (23.7%) were hypertension related. Mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 167.4 ± 18.2 and 98.6 ± 13.5, respectively, at presentation. Although, hypertension-related admissions were 23.7% of total admissions, there was an excess of mortality associated with SH complications (42.9%). Stroke was the commonest, and it accounted for 44.4% of cases. Stroke had the highest mortality (39.3%), followed by chronic kidney disease (36.6%); hypertensive emergencies (30.9%) and hypertensive heart failure had the lowest intrahospital mortality (27.5%). In conclusion, SH-related admissions are common among medical admissions in Bauchi Nigeria and are associated with high mortality. Community interventions that promote early diagnosis and reduction of cardiovascular risk profiles are urgently needed to reduce SH deaths.